Evolutionary relationship and population structure of domestic Bovidae animals based on MHC-linked and neutral autosomal microsatellite markers - Guang-Xin, E.; Li-Peng Chen; Dong-Ke Zhou; Bai-Gao Yang; Jia-Hua Zhang; Yong-Ju Zhao; Qiong-Hua Hong; Yue-Hui Ma; Ming-Xing Chu; Lu-Pei Zhang; Wang-Dui Basang; Yan-Bin Zhu; et al. (Elsevier, 2020)
Major histocompatibility complex (MHC) genes are critical for disease resistance or susceptibility responsible for host-pathogen interactions determined mainly by extensive polymorphisms in the MHC genes. Here, we examined the diversity and phylogenetic pattern of MHC haplotypes reconstructed using three MHC-linked microsatellite markers in 55 populations of five Bovidae species and compared them with those based on neutral autosomal microsatellite markers (NAMs). Three-hundred-and-forty MHC haplotypes were identified in 1453 Bovidae individuals, suggesting significantly higher polymorphism and heterozygosity compared with those based on NAMs. The ambitious boundaries in population differentiation (phylogenetic network, pairwise FST and STRUCTURE analyses) within and between species assessed using the MHC haplotypes were different from those revealed by NAMs associated closely with speciation, geographical distribution, domestication and management histories. In addition, the mean FST was significantly correlated negatively with the number of observed alleles (NA), observed (HO) and expected (HE) heterozygosity and polymorphism information content (PIC) (P < 0.05) in the MHC haplotype dataset while there was no correction of the mean FST estimates (P> 0.05) between the MHC haplotype and NAMs datasets. Analysis of molecular variance (AMOVA) revealed a lower percentage of total variance (PTV) between species/groups based on the MHC-linked microsatellites than NAMs. Therefore, it was inferred that individuals within populations accumulated as many MHC variants as possible to increase their heterozygosity and thus the survival rate of their affiliated populations and species, which eventually reduced population differentiation and thereby complicated their classification and phylogenetic relationship inference. In summary, host-pathogen coevolution and heterozygote advantage, rather than demographic history, act as key driving forces shaping the MHC diversity within the populations and determining the interspecific MHC diversity.